The Genealogical Imagination : Two Studies of Life over Time - Jackson, Michael, 1940- (Book collections on Project MUSE., 2021)
"The Genealogical Imagination comprises two thematically-related books. Though both explore intergenerational transitivity and trauma, they draw on very different empirical sources and discursive techniques. While the first book is based on the author's extensive fieldwork among the Kuranko of Sierra Leone, the second book, which is largely a work of the imagination, draws on episodes from Jackson's family history and fieldwork experiences in Aboriginal Australia"--